Primary malignant melanoma of the vagina: a case report and review of the current treatment options - (:unkn) unknown (ELSEVIER SCIENCE BV, 2005)
A case with primary malignant melanoma located in the posterior lower third of the vagina was encountered and treated by surgery, postoperative immunotherapy and chemotherapy. The tumor was close to the anal sphincter and posterior exenteration was done to achieve tumor-free surgical margins. The need for such radical treatment prompted us to review the literature and discuss our case with the rarest localization of the tumor in the vagina. We focused on the treatment options and the possible complication that may arise during the treatment of the primary malignant melanoma of the vagina. The need for radical surgery was discussed and the current treatment options were reviewed. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: vagina; melanoma; posterior exenteration; THERAPY; MM